High-fidelity readout of trapped-ion qubits - Myerson, A; Szwer, D; Webster, S; Allcock, D; Curtis, M; Imreh, G; Sherman, J; Stacey, D; Steane, A; Lucas, D (American Physical Society, 2008)
We demonstrate single-shot qubit readout with a fidelity sufficient for fault-tolerant quantum computation. For an optical qubit stored in 40Ca+ we achieve 99.991(1)% average readout fidelity in 10^6 trials, using time-resolved photon counting. An adaptive measurement technique allows 99.99% fidelity to be reached in 145 μs average detection time. For 43Ca+, we propose and implement an optical pumping scheme to transfer a long-lived hyperfine qubit to the optical qubit, capable of a theoretical fidelity of 99.95% in 10 μs. We achieve 99.87(4)% transfer fidelity and 99.77(3)% net readout fidelity.